Effects of in-store marketing on food and beverage purchases: a longitudinal study of households with children - Anna H Grummon; Joshua Petimar; Alyssa J Moran; Emma Anderson; Peter Lurie; Sara John; Eric B Rimm; Anne N Thorndike (Cambridge University Press, 2024)
Abstract Objective: Most food retailers display foods in prominent locations as a marketing strategy (i.e. 'placement promotions'). We examined the extent to which households with children change their food and beverage purchases in response to these promotions. Design: We analysed a novel dataset of all products promoted in two supermarkets from 2016 to 2017, including promotion dates and locations (e.g. aisle endcaps and front registers). We linked promotions to all purchases from the supermarkets from 2016 to 2017 by a cohort of households with children. We calculated the number of weekly promotions in each of thirteen food and beverage groups (e.g. bread; candy) and used fixed effects regressions to estimate associations between number of weekly promotions and households' weekly food purchases, overall and by Supplemental Nutrition Assistance Program (SNAP) participation. Setting: Two large supermarkets in Maine, USA. Participants: Eight hundred and twenty-one households with children. Results: Most promotions (74 %) were for less healthy foods. The most promoted food groups were sweet and salty snacks (mean = 131·0 promotions/week), baked goods (mean = 68·2) and sugar-sweetened beverages (mean = 41·6). Households generally did not change their food group purchases during weeks when they were exposed to more promotions for those groups, except that a 1-sd increase in endcap candy promotions (about 1 promotion/week) was associated with $0·19/week (about 14·5 %) increase in candy purchases among SNAP nonparticipants (adjusted P < 0·001). Conclusions: In-store placement promotions for food groups were generally not associated with purchases of promoted food groups, perhaps because exposure to unhealthy food marketing was consistently high. Substantial changes to in-store food marketing may be needed to promote healthier purchases.